SECURITY PERCEPTION AND CYBER SECURITY IN THE CONTEXT OF INTERNATIONAL RELATIONS, AN EVALUATION ABOUT MEDITERRANEAN, BLACKSEA AND EUROPE REGIONS - Vahit GÜNTAY (Fırat University, 2019)
Conflict fact in the nature of international relations and brought with it security studies are reshaping with conditions of the period day by day. Borders of the interstates or infinities with technological developments have added a new security concern. Cyber attacks and its problems as a conclusion in international security have revealed a new diplomacy and conflict area in the context of international relations.Especially critical infrastructures and these infrastructures’ diplomatic importance in the context of international relations have expedited the studies and meetings in this area and created awareness. Cyber attacks which became a deterrence mechanism for international actors and cyber terrorism-wars which occupy the international agenda in the cyber security area will have wide media coverage of states in the long term. Cyber security which have special and different studying area in international relations is increasing the significance of security for Turkish Republic of Northern Cyprus and Cyprus Island specific to Mediterranean. On the other hand whether Black Sea states have a deterrence in the manner of cyber attacks or the results in diplomacy have gained importance with some developments in more recent times. Black Sea states’ deterrence and attack capability have come into prominence with their own interior structurings. The harmony of European Union states in this area, security developments with its results and policies for these states and the meaning of borders have also gained importance for the future. Sincerity as the most important factor of security and applying realpolitik are the emphasized points in this study. Within this context regional evaluations have been discussed about security perception, cyber security and it is aimed to present a perspective in the base of cyber security.